2022
DOI: 10.1038/s41598-022-14400-w
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral radiomics features on preoperative thin-slice CT images can predict the spread through air spaces of lung adenocarcinoma

Abstract: The spread through air spaces (STAS) is recognized as a negative prognostic factor in patients with early-stage lung adenocarcinoma. The present study aimed to develop a machine learning model for the prediction of STAS using peritumoral radiomics features extracted from preoperative CT imaging. A total of 339 patients who underwent lobectomy or limited resection for lung adenocarcinoma were included. The patients were randomly divided (3:2) into training and test cohorts. Two prediction models were created us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Previous studies have investigated the value of radiomics features for STAS prediction, mostly in patients with early stage surgically resected lung adenocarcinoma. 23 24 25 26 27 28 29 44 45 46 47 48 Most previous studies constructed radiomics models using radiomics features, with the number of selected features ranging from 2 to 12, and reported the performance of the model using the AUC, which ranged from 0.63 to 0.99. Although all previous studies concluded that radiomics features were useful for the preoperative prediction of STAS, the actual added value of radiomics to the conventional prediction model and the association with survival were rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the value of radiomics features for STAS prediction, mostly in patients with early stage surgically resected lung adenocarcinoma. 23 24 25 26 27 28 29 44 45 46 47 48 Most previous studies constructed radiomics models using radiomics features, with the number of selected features ranging from 2 to 12, and reported the performance of the model using the AUC, which ranged from 0.63 to 0.99. Although all previous studies concluded that radiomics features were useful for the preoperative prediction of STAS, the actual added value of radiomics to the conventional prediction model and the association with survival were rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This non-invasive method has shown its potential usefulness for the identification of internal tumor heterogeneity ( 7 , 8 ). In recent decades, radiomics has been well proven in the identification, staging, and evaluation of lung cancer ( 9 ). Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…This non-invasive method has shown its potential usefulness for the identification of internal tumor heterogeneity (7,8). In recent decades, radiomics has been well proven in the identification, staging, and evaluation of lung cancer (9). Wang et al found that CT imaging features characteristic of PIMA might provide prognostic information and individual risk assessment in addition to clinical factors (10).…”
Section: Introductionmentioning
confidence: 99%
“…7,9 Some studies have reported the usefulness of radiomic features derived from intratumoral and peritumoral regions for predicting tumor spread in air space (STAS). [12][13][14] STAS is also associated with EGFR mutations. 14 Moreover, the predictive model by Wang et al established that both the intratumoral and peritumoral regions are important for predicting EGFR mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the usefulness of radiomic features derived from intratumoral and peritumoral regions for predicting tumor spread in air space (STAS). 12 , 13 , 14 STAS is also associated with EGFR mutations. 14 Moreover, the predictive model by Wang et al.…”
Section: Introductionmentioning
confidence: 99%